Implementasi Corporate Social Responsibility (Csr) Perspektif Etika Bisnis Islam - Uswatun Khasanah Uswatun Khasanah; Fetria Eka Yudiana (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
Indonesia is a country rich in natural resources. These natural resources will be of value if managed properly. This can lead to the creation of a business or business by utilizing existing natural resources. Tempura is one of the business districts in Magelang Regency, ranging from small-scale business centers to industrial scale. In Islam, a business person is not allowed to do business only to seek maximum profit. But you have to pay attention to ethics in doing business. This research examines the implementation of Islamic business ethics in the Brambang Salam restaurant, which is located in a boarding school environment. The research method used is qualitative research. The data used in this study are primarily in the form of interviews and documentation of informants. The sources used in this study included one manager, 2 employees, 3 students, and 3 administrators of the Islamic boarding school. The results of this study reveal that the Griya Dhahar Brambang Salam restaurant has carried out social responsibility based on Islamic business ethics. This can be seen in various aspects. First, the responsibility between humans and Allah, such as paying part of the electricity and water costs. Second, human-human responsibilities such as giving holiday allowances and recruiting employees. Third, social responsibility between humans and the environment, such as providing community service and making special waste disposal sites.